2018
DOI: 10.3390/ijms19092541
|View full text |Cite
|
Sign up to set email alerts
|

Low P16INK4A Expression Associated with High Expression of Cancer Stem Cell Markers Predicts Poor Prognosis in Cervical Cancer after Radiotherapy

Abstract: Previous studies have suggested that cancer stem cells (CSCs) resisted radiotherapy and chemotherapy. P16INK4A is a biomarker for cervical carcinogenesis and reduces proliferation of stem cells. We aimed to investigate the expression and clinical significance of cyclin-dependent kinase inhibitor 2A (P16INK4A), sex determining region Y-box 2 (SOX2), and Aldehyde dehydrogenase 1 family, member A1 (ALDH1A1) in cervical cancer treated with radiotherapy and cervical cell line models. The expressions of P16INK4A, SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 33 publications
1
27
1
Order By: Relevance
“…To date, p16 expression pattern remains controversial, because there is no fundamental justification yet as to whether cytoplasmic/nuclear or only nuclear staining should be taken as positive [15]. As other authors have found [5,32], there was no association between p16 expression or location and pathological variables in our study, but we did find that the lack of nuclear p16 allowed SCCC to acquire aggressive features both in tumors and in vitro. This interesting finding goes some way to explaining the paradoxical p16 overexpression in SCCC.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…To date, p16 expression pattern remains controversial, because there is no fundamental justification yet as to whether cytoplasmic/nuclear or only nuclear staining should be taken as positive [15]. As other authors have found [5,32], there was no association between p16 expression or location and pathological variables in our study, but we did find that the lack of nuclear p16 allowed SCCC to acquire aggressive features both in tumors and in vitro. This interesting finding goes some way to explaining the paradoxical p16 overexpression in SCCC.…”
Section: Discussioncontrasting
confidence: 74%
“…The potential therapeutic value of p16 is also to be elucidated. On the one hand, depletion of p16 has been shown to promote chemo-and radioresistance in HeLa cells [32]. On the other hand, it has been suggested that p16 could be a therapeutic target in CC, since its knockdown inhibits cell proliferation, migration and invasion in SiHa and HeLa cell lines [43] and sensitizes SiHa cells to cisplatin [35].…”
Section: Discussionmentioning
confidence: 99%
“…Normally, the expression of P16 increases with age which results in a decrease of the renewal activity of stem cells. In conditions of inhibition / low P16 expression, there will be high expression of cancer stem cells which results in increased ability of self-renewal of cancer stem cells 16 . The sensitivity, specificity and accuracy of P16 biomarker to diagnose SCC of cervix is 96.0%, 88.2% and 91.7%, respectively 17 .…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we went ahead examining the downstream regulators such as CDK4 and CDK6. The kinase CDK6 is not only implicated in cancer for its oncogenic role, but for regulating the stem cell pool dynamics that facilitates recurrence . Altered stem cell marker expressions in response to KD and Hsp90 inhibition in matrix based manner (2D vs 3D) suggests their independent influence on regulating the stem cell pool dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The kinase CDK6 is not only implicated in cancer for its oncogenic role, but for regulating the stem cell pool dynamics that facilitates recurrence. 31,33,34 Altered stem cell marker expressions in response to KD and Hsp90 inhibition in matrix based manner (2D vs 3D) suggests their independent influence on regulating the stem cell pool dynamics. However, in KD combination with 17AAG, this regulation is found to be lost.…”
Section: Discussionmentioning
confidence: 99%